Proposing a multi-method phenomenological approach in exploring the perceived daily life experiences of people with dementia in their dementia care environments and immediate outdoor settings - Mercieca, Alexia; Scott, Iain; Ward Thompson, Catharine; Wilkinson, Heather (Frontiers in Dementia, 2025)
The environment in this study is presented primarily drawing on the theoretical definition of home, and its experience and meaning to the individual with dementia, with an interest in access to outdoors. Notions of perception, cognitive image and affordance are central to the sense of home, and in turn the sense of self that this may inform and support. This theoretical framework informs the multi-method phenomenological approach proposed, through themes of spatial legibility, cultural appropriateness, fascination, user-centredness and personalisation. The novelty of the methodological toolkit lies in the incorporation of methods that have been traditionally used in research with people with dementia as the basis of the framework, but which are supplemented by additional layers developed from conventional architectural tools to create a more visual representation of the environmental experience. Despite its apparent complexity, the methodology yields a very clear and precise image of the person's presence in her surroundings, at once providing a location in space and time, her mood and engagement, as well as a layering of the affordances that may have informed her behavior. This method was developed as part of this research, and remains unique to it. Its innovation lies in the progression of the DCM tool, the integration of the notion of affordances and architectural mapping techniques to propose a holistic depiction of the care experience of people with dementia.